Staring at the cold sun: Blue light regulation is distributed within the genus Acinetobacter - Golic, Adrián Ezequiel (2013)
We previously showed that the opportunistic nosocomial pathogen Acinetobacter baumannii is able to sense and respond to light via BlsA, a BLUF (Blue-Light-sensing Using FAD)-domain photoreceptor protein. Here, we extend our previous studies showing that light regulation is not restricted to A. baumannii, but rather widespread within the genus Acinetobacter. First, we found that blue light modulates motility and biofilm formation in many species of the genus, including members of the Acinetobacter calcoaceticus-A. baumannii complex. In many of these species blue light acts as a key factor guiding the decision between motility or sessility at 24uC, whereas in A. baumannii, light inhibits both motility and biofilm formation. We also show that light regulation of motility occurred not only at 24uC but also at 37uC in non-A. baumannii species, contrasting the situation of A. baumannii which only shows photoregulation at 24uC. Second, we show that Acinetobacter baylyi (strain ADP1) BLUF-photoreceptors can functionally replace in vivo the A. baumannii 17978 BlsA protein and that the pathways leading to biofilm formation are inversely regulated at 24uC between these two microorganisms. Finally, we found the presence of predicted genes coding BLUF-containing proteins in all Acinetobacter sequenced genomes, even though the copy number is variable among them. Phylogenetic analysis suggests a common origin for all BLUF domains present in members of this genus, and could distinguish well-differentiated clusters that group together BLUF homologs from different species, a situation particularly clear for members of the ACB complex. Despite a role played by these BLUF domain-containing proteins in the photoregulation observed in the members of the genus Acinetobacter is a likely scenario given our findings in A. baumannii and A. baylyi, further research will contribute to confirm this possibility.